Comparison of Surgical Outcomes by the Age at the Time of Surgery in the Treatment of Congenital Scoliosis: More than 10-year Follow-up. Issue 1 (April 2016) - Chang, Dong-Gune; Kim, Jin-Hyok; Na, Ki-Ho; Lee, Jung-Hee; Suk, Se-Il
Introducion: There is little information reported about the long term follow-up of surgical outcomes that pertain to the timing of surgery for congenital scoliosis in children under age 20 years. This study is to compare the surgical outcomes of posterior vertebral column resection (PVCR) for congenital scoliosis in children less than 20 years of age. Materials and Methods: Forty-five congenital scoliosis patients ( N  = 45) under age 20 at the time of surgery were treated by PVCR and fusion with PSF. These cases were retrospectively studied and had a minimum 10-year follow-up. We assigned patients into two groups: Group 1 ( N  = 19) patients who had surgery before 10 years of age, Group 2 ( N  = 26) those who had surgery after 10 years of age. Results: In Group 1, the mean Cobb angle of the main curve was 44° before surgery, 10.2° after surgery, and 14.2° at last follow-up. In Group 2, the mean Cobb angle of the main curve was 48.7° before surgery, 17.2° after surgery, and 20.4° at last follow-up. The mean operative time was 189 minute (range: 70 to 405 minute) in Group 1 and 245 minute (range: 80 to 395 minute) in Group 2. The mean estimated blood loss (EBL) was 1285 mL (range: 270 to 3000 mL) in Group 1 and 2376 mL (range: 600 to 6000 mL) in Group 2. The mean fused segments were 3.3 in Group 1 and 4.6 in Group 2. Conclusions: In congenital scoliosis patients, PVCR is an effective procedure for the management of congenital scoliosis under age 20. PVCR and fusion with PSF for congenital scoliosis before the age of 10 years had significantly better deformity correction compared with the group after the age of 10 years and did not cause crankshaft phenomenon. The mean operative time and EBL in children under age 10 were both significantly less compared with children between 10 and 20 years of age.